Monetary Integration in the Southern Cone: Mercosur is not like the EU? - Ansgar Belke; Daniel Gros (Oesterreichische Nationalbank (OeNB), 2002)
Evaluating the costs and benefits of exchange rate stability requires a somewhat different approach for Mercosur than for the EU. EU member countries are highly integrated in terms of trade in goods and services. By contrast, trade integration within Mercosur is much more limited, intra-area exchange rates are thus less important than the exchange rate vis-a-vis the dollar and the euro. This contribution analyses the impact of both aspects of financial volatility (exchange rate and interest rate volatility) on investment and labour markets in the Southern Cone, finding that both exchange rate variability (mainly against the dollar and the euro) and (domestic) interest rate volatility have a significant dampening impact on employment and investment, as predicted by our theoretical model.
Keywords: E42; F36; F42; 330; currency union; exchange rate and interest rate variability; job creation; Mercosur; option value effects